1994
DOI: 10.1093/geront/34.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Widows in Retirement Communities: The Social Context of Subjective Well-being

Abstract: This study focuses on why some widows were satisfied in retirement communities and some were not. Satisfied widows were more socially active and were the majority in the community. Widows and married differed in social interactions contingent on which group was in the majority. The ratio of marrieds to widows in a community may lead to different social interaction in the two groups which, in turn, may influence widows' satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…(1) 37 persons (aged 73-94) receiving care at home (Nunley, Hall, and Rowles 2000), (2) 88 persons (aged 55-95) in Australia (Lennings 2000), and (3) 233 widows living in retirement communities (age not reported) (Hong and Duff 1994). Compared with younger persons in those samples, older persons were more likely to report lower LS.…”
Section: Age and Life Satisfactionmentioning
confidence: 99%
“…(1) 37 persons (aged 73-94) receiving care at home (Nunley, Hall, and Rowles 2000), (2) 88 persons (aged 55-95) in Australia (Lennings 2000), and (3) 233 widows living in retirement communities (age not reported) (Hong and Duff 1994). Compared with younger persons in those samples, older persons were more likely to report lower LS.…”
Section: Age and Life Satisfactionmentioning
confidence: 99%
“…In a more current study, Hong and Duff (1994) investigated the well-being of widows in seven retirement communities in two western states. Individual-level analysis of well-being was related to community measures of the ratios of married people (marrieds) to widows.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Sherman 1975;Stephens and Bernstein 1984). A more recent study has found that satisfaction among widows was influenced by their level of social activity and the village's marital ratios (Hong and Duff 1994).…”
Section: Introductionmentioning
confidence: 99%